Analisis Desain dan Implementasi Kebijakan Penanganan Stunting Kota Palangka Raya - Gabriel Keintjem; Jeanita Remilka Tabitha; Sinta Sinta; Syintha Elia Putri (Professional: Jurnal Komunikasi dan Administrasi Publik, 2026)
Stunting remains one of the major development issues that affects the quality of human resources and requires intervention through integrated policies. Palangka Raya City showed a decline in stunting prevalence from 28% in 2023 to 19.1% in 2024, making it an interesting case to examine from the perspective of policy design and implementation. This study aims to analyze the design and implementation of stunting reduction policies in Palangka Raya City, as well as to identify the factors influencing the effectiveness of their implementation. This research uses a descriptive qualitative method, with data collected through observation, interviews, and documentation. The findings show that the implementation of stunting reduction policies is carried out through cross-sector collaboration involving regional government agencies, integrated health posts (posyandu), health workers, communities, and various other social actors. Program interventions are implemented through assistance for children affected by stunting, distribution of nutritious food aid, health education, and the Free Nutritious Meal Program.In addition, community social capital also supports the success of the program through the participation of cadres and local donors. However, policy implementation still faces several challenges, including coordination among actors, data integration, and program sustainability. This study indicates that the success of stunting reduction is influenced by the synergy between policy design, collaborative implementation, and the continuous involvement of stakeholders.